Mapping of Mobile Technology Publications: A Scientometric Approach - R., Santhakumar; Kaliyaperumal, K. (DESIDOC Journal of Library & Information Technology, 2014)
This paper focus on the growth and development of mobile technology in terms of publication output as reflected in engineering index database. During 2003-2012, a total of 144567 publications were published in the field. The average number of publications published per year was 14456.7 and the highest numbers of publications 20318 were published in 2011. Authors from China have contributed maximum number of publications compared to the other countries and India stood 7th in terms of productivity in this period. The most prolific author is Wang, Wei who contributed 223 publications followed by Barolli, Leonard with 160 publications. Institute of Electrical and Electronic Engineering (IEEE), New York (USA) is the highly contributed institution with 1248 publications followed by South-East University (China) with 508 publications, Nokia Research Centre, Cambridge (UK) with 502 publications and School of Electrical and Electronic Engineering, Nanyang Technological University (Singapore) with 290 publications. The relative growth rates (RGR) has decreased from 2004 (0.98) to 2012 (0.13) in the span of 10 years. The doubling time (DT) has gradually increased from 0.71 in 2004 to 5.15 in 2012. http://dx.doi.org/10.14429/djlit.34.5825